Experimental study of the radiation shielding characteristics of new PbO– Na2O–B2O3–BaO glasses - M.I. Sayyed; U. Rilwan; K.A. Mahmoud; Mohamed Elsafi (Nuclear Engineering and Technology, 2024)
This work synthesized four glass samples with a fixed ratio of PbO to Na2O and a variable ratio of BaO to B2O3. The linear attenuation coefficient (LAC) (μ, cm−1) and additional attenuator parameters were determined experimentally using a semiconductor detector and different gamma sources. The comparison was carried out between the experimental and the XCOM calculated results, with good agreement emerging between the two results. The impacts of the BaO substituting for the B2O3 on fabricated PNBB glasses' radiation shielding properties were discussed. By increasing the BaO substitution concentration between 10 and 25 mol.%, the LAC μ values (cm−1) increased by 76.60 %, 13.81 %, 12.56 %, and 12.52 % for the respective γ-ray energies of 0.059, 0.662, 1.173, and 1.332 MeV. The μ value reduction with raised gamma energy values increased the values of the calculated half-value thickness (Δ0.5) as a result of the μ and Δ0.5 values' reverse proportionality. Other shielding parameters such as the lead equivalent thickness (Δeq) and radiation protection efficiency were also determined for the present PNBB glass samples.